Eksistensi Lembaga Adat Melayu Jambi Dalam Penyelesaian Sengketa Masyarakat Adat - Herlina Manik (Jurnal Selat, 2019)
Disputes that arise in the community can disrupt the public order. For this reason, efforts are needed so that’s every dispute can be resolved so that the balance in the community order can be restored. The purpose of this study is to determine the extent of the existence of customary institutions in resolving disputes and also to find out what processes or steps are taken by traditional institutions in resolving disputes. This research was conducted in Jambi. This type of researsh is sociological juridical. Data collection was conducted through interviews, data were analyzed by qualitative analysis and presented descriptively. The results of the study show that the existence of the Jambi Malay Customary Institution in the settlement of indigenous peoples' customary law disputes still exists and still continues today. The existence of the Jambi Malay Customary Institution can be seen from its arrangement in the Jambi Province Regional Regulation (PERDA) Number 5 of 2014 concerning the Jambi Malay Customary Institution. The dispute resolution prosses are carried out in several stages, namely: the stage of summoning the parties, the stage of summoning the witness, the stage of the deliberation process and closing. After going through the deliberation process, the mediator will provide a decision / solution that if accepted by the parties will be made in the form of an agreement. But if the parties cannot accept it, the mediator gives input to proceed to the court's formal path. Jambi Province's Regional Regulation Number 5 of 2014 concerning Jambi Malay Customary Institutions can continue to be socialized and Jambi LAM is expected to be increasingly active in carrying out its duties and functions so that Jambi traditional law can be enforced in community life.